Cross evaluation of experience level and teaching approaches in college table tennis physical education students - Maso, Denise Anne M.; Salangsang, Marie Toni A. (2021)
This study was conducted to determine which approach is more effective between Random and Blocked practice in teaching Physical Education. It also focused on the effect of Random practice in motor-learning and memory capacity of individuals in learning a sport. The two approaches were used to teach the forehand and backhand skills of Table Tennis. Sixty-four students of the University of the Philippines-Los Baños (UPLB) taking the course PE 2 Table Tennis were chosen as subjects and they were classified as Beginners, Intermediate and Advance players. These students were assigned into two training groups; the Blocked Practice and the Random Practice. Afterwards, both groups went through pre-test, post-test and retention test. With the use of a device called Robo-Pong, their performances were observed and recorded before and after the trainings. Using the data gathered, it was determined that all groups improved since they achieved higher scores from pre-test to post-test through Blocked and Random practice. Meanwhile, in the post-test and retention scores, Beginners and Intermediate players had higher mean scores in the Random group.
Keywords: Table tennis; Teaching methods